Economic structure, key sectors and exports in Mexico and El Salvador - Pérez-Santillán, Lesbia (2023)
The relationship between economic growth and the structure of the economy is a relevant aspect when analyzing the factors that promote or limit development. The sectors that characterize an economy and its internal and external productive network explain the trajectory and possibilities of economic development. This paper examines the economic structures of El Salvador and Mexico. The traditional analysis of key sectors is complemented with the estimation of the pure linkages to consider the size of the sectors. The results show that in El Salvador most of the key sectors are not the largest in the economy; while in contrast, in Mexico some key sectors are also important due to their size. The foregoing, together with the analysis of the indicators of the imported content of exports and the participation of the sectors in value added and employment, provides a more complete picture of the productive structure and its recent implications for economic growth and response to shocks such as the Covid 19 pandemic.